Polityka kursu walutowego w Polsce w latach 1990 - 1994 - Kowalski, Tadeusz (Wydział Prawa i Administracji UAM, 1994)
The purpose of the paper was to investigate the manner in which exchange rate policy was carried out in Poland in the years 1990 - 1994. Relations between the exchange rate policy and monetary policy as well as changes in the foreign trade structure after the implementation of exchange policy have been analysed and a differentiation between a fixed exchange rate and the crawling peg has been made. Despite the controversy over the first phase ('overshooting' and delayed introduction of the crawling peg), the foreign exchange rate policy in the investigated period deserves to be evaluated very highly. A recommendation drafted in the paper proposes a change in the structure of the currency basket (which should consist of ECU and USD only) and gradual lowering of the crawling peg rate until a fixed exchange rate is achieved when inflation rate is reduced to a one digit level.
Foreign exchange rate policy in Poland in the years 1990 - 1994